De novo stress urinary incontinence after pelvic organ prolapse surgery in women without occult incontinence - Alas A. (2017)
© 2016, The International Urogynecological Association. Introduction and hypothesis: There is a paucity of data evaluating the risk of de novo stress urinary incontinence (SUI) after surgery for pelvic organ prolapse (POP) in women with no preoperative occult SUI. We hypothesized that apical suspension procedures would have higher rates of de novo SUI. Methods: This was a retrospective database review of women who had surgery for POP from 2003 to 2013 and developed de novo SUI at ≥6 months postoperatively. Preoperatively, all patients had a negative stress test and no evidence of occult SUI on prolapse reduction urodynamics. The primary objective was to establish the incidence of de novo SUI in women with no objective evidence of preoperative occult SUI after POP surgeries at ≥6 months. Results: A total number of 274 patients underwent POP surgery. The overall incidence of de novo SUI was 9.9 % [95 % confidence interval (CI) 0.07–0.14]. However, the incidence of de novo SUI in those with no baseline complaint of SUI was 4.4 % (95 % CI 0.03–0.1). There was no difference in de novo SUI rates between apical [9.7 % (n = 57)] and nonapical [10.5 %, (n = 217] procedures (p = 0.8482). Multivariate logistic regression identified sacrocolpopexy [adjusted odds ratio (OR) 4.54, 95 % CI 1.2–14.7] and those with a baseline complaint of SUI (adjusted OR 5.1; 95 % CI 2.2–12) as risk factors for de novo SUI. Conclusions: The incidence of de novo SUI after surgery for POP without occult SUI was 9.9 %. We recommend counseling patients about the risk of de novo SUI and offering a staged procedure.